Kedudukan Karya Seni Digital dalam Sistem Non-Fungible Token (NFT) Terhadap Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Chrisnando, Gabriel Rhema; Santoso, Budi; Rahmanda, Bagus (Law, Development and Justice Review, 2023)
Non-fungible tokens (NFTs) make it easier for artists to utilize the moral and economic rights to their artworks in digital form. Unfortunately, the implementation of NFTs is still not accompanied by special regulations governing it. Law Number 28 of 2014 concerning Copyright can at least be a reference for its regulation because after all, one of the assets underlying the sale and purchase of NFTs is a work of art which is also protected by copyright. The purpose of this study is to analyze the position and legal protection of digital artworks in the NFT system from the perspective of Law Number 28 of 2014 concerning Copyright. This research uses a normative juridical approach method by taking secondary data sources and supporting data in the form of interviews with NFT creators which are then analyzed qualitatively. The results showed that digital artworks in the NFT system have the same position as works of art in general as they are also protected by copyright under Article 40 of Law Number 28 of 2014 concerning Copyright. However, there are several aspects in its implementation that are different from the Copyright Law, such as the royalty acquisition mechanism which is not based on a license agreement, but uses a smart contract which has become a default option offered in the NFT marketplace platform system. The NFT marketplace platform and the government exist as parties in charge of protecting copyright law.